Fietsinfrastructuur. - Bendiks, Stefan; Degros, Aglaée (Rotterdam : nai010, 2013)
"Cycling is experiencing a worldwide revival. It is a sustainable, affordable and above all trendy alternative to the car and public transport. Experiments in new cycling facilities are underway everywhere. Cycle Infrastructure includes international examples, interviews with the makers of prominent cycling routes and a glimpse at future innovations. Cycle Infrastructure is an inspiring handbook for anyone interested in the development, design and promotion of high-quality cycling routes. The goal is to activate the full potential of cycling for the (urban) landscape and to consider cycling infrastructure as an integral design challenge instead of purely an issue of traffic engineering."--P. [4] of cover.
boek